Books
in black and white
Main menu
Share a book About us Home
Books
Biology Business Chemistry Computers Culture Economics Fiction Games Guide History Management Mathematical Medicine Mental Fitnes Physics Psychology Scince Sport Technics
Ads

Elementary differential equations 7th edition - Boyce W.E

Boyce W.E Elementary differential equations 7th edition - Wiley publishing , 2001. - 1310 p.
ISBN 0-471-31999-6
Download (direct link): elementarydifferentialequat2001.pdf
Previous << 1 .. 328 329 330 331 332 333 < 334 > 335 336 337 338 339 340 .. 486 >> Next

1. Linear 2. Homogeneous
3. Exact 4. Linear equation in x(y)
5. Exact 6. Linear
2 dy dy
7. Letting u = x yields --------- = 2x and thus
dx du
du 3
- 2yu = 2y which is linear in u(y). dy
34 Miscellaneous Problems
8. Linear 9. Exact
10. Integrating factor depends on x only 11. Exact
12. Linear 13. Homogeneous
14. Exact or homogeneous 15. Separable
16. Homogeneous 17. Linear
18. Linear or homogeneous 19. Integrating factor depends on x only
20. Separable 21. Homogeneous
22. Separable 23. Bernoulli equation
24. Separable 25. Exact
26. Integrating factor depends on x only 27. Integrating factor depends on x only
28. Exact 29. Homogeneous
30. Linear equation in x(y) 31. Separable
32. Integrating factor depends on y only.
35
CHAPTER 3
Section 3.1, Page 136
-TX rt T ? T / rt n 2 rt
3. Assume y = e , which gives y = re and y = re .
2 rt
Substitution into the D.E. yields (6r -r-1)e = 0.
rt
Since e no, we have the characteristic equation 6r2-r-1 = 0, or (3r+1)(2r-1) = 0. Thus
r = -1/3, 1/2 and y = c1et/2 + c2e-t/3.
2
5. The characteristic equation is r + 5r = 0, so the roots
are r1 = 0, and r2 = -5. Thus
0t -5t -5t
y = c1e + c2e = c1 + c2e .
2
7. The characteristic equation is r - 9r + 9 = 0 so that
r = (9\j 81-36 )/2 = (93^/5)/2 using the quadratic
formula. Hence
y = c1exp[(9 + 3^/5 )t/2] + c2exp[(9-3^/5 )t/2].
rt
10. Substituting y = e in the D.E.
we obtain the characteristic
2
equation r + 4r + 3 = 0, which has the roots r1 = -1, r2 = -3.
-t -3t
Thus y = c1e + c2e and
-t -3t
y = -c1e - 3c2e .
Substituting t = 0 we then have c1 + c2 = 2 and -c1 - 3c2 = -1,
yielding c1 = 5/2 and
5 -t 1 -3t
c2 = -1/2. Thus y = e - e
2 2 2
and hence y ^ 0 as t ^ .
2
15. The characteristic equation is r + 8r - 9 = 0, so that r1 = 1 and r2 = -9 and the general solution is
t -9t
y = c1e + c2e . Since the I.C. are given at t = 1, it
is convenient to write the general solution in the form
(t-1) -9(t-1)
y = k1e + k2e . Note that
-1 9
c1 = k1e and c2 = k2e . The advantage of the latter form of the general solution becomes clear when we apply
36
Section 3 . 1
is y(t ) = ce + ce .
1 2
3
c - c = - , yielding
1 2 4
(t) = 1t - t
e - e = 0 or
4
the I.C. y(1) = 1 and y/(1) = 0. This latter form of y
(t-1) -9(t-1)
gives y = k1e - 9k2e and thus setting t = 1 in
y and y' yields the equations k2 + k2 = 1 and
ki - 9k2 = 0. Solving for k2 and k2 we find that
(t-1) -9(t-1) (t-1)
y = (9e + e )/10. Since e has a positive
exponent for t > 1, y ^ as t ^ .
17. Comparing the given solution to Eq(17), we see that r = 2
1
and r = -3 are the two roots of the characteristic 2
2
equation. Thus we have (r-2)(r+3) = 0, or r + r - 6 = 0
as the characteristic equation. Hence the given solution
is for the D.E. y" + y' - 6y = 0.
19. The roots of the characteristic equation are r = 1, -1
t -t
5
y(0) = c + c = and y'(0
124
1 t -t
y(t) = e + e . From this
4
2t
e = 4 or t = ln2. The second derivative test or a graph of the solution indicates this is a minimum point.
-t 2t
21. The general solution is y = c1e + c2e . Using the I.C.
we obtain c1 + c2 = a and -c1 + 2c2 = 2, so adding the two
equations we find 3c2 = a + 2. If y is to approach zero
as t , c2 must be zero. Thus a = -2.
24. The roots of the characteristic equation are given by
-2t (a-1)t
r = -2, a - 1 and thus y(t) = ce + ce . Hence,
12
for a < 1, all solutions tend to zero as t . For a > 1, the second term becomes unbounded, but not the first, so there are no values of a for which all solutions become unbounded.
2
25a. The characteristic equation is 2r + 3r - 2 = 0, so
r1 = -2 and r2 = 1/2 and y = c1e 2t + c2et/2. The I.C.
1
yield c2 + c2 = 2 and -2c2 + c2 = -p so that c2 = (1 + 2b)/5 and c2 = (4-2b)/5.
Section 3.1
37
25c.
27.
28.
30.
34.
37.
-2t
From part (a), if b = 2 then y(t) = e and the solution simply decays to zero. For b > 2, the solution becomes unbounded negatively, and again there is no minimum point.
-t
The second solution must decay faster than e , so choose
-2t -3t
e or e etc. as the second solution. Then proceed as in Problem 17.
Let v = y', then v' = y" and thus the D.E. becomes 22 tv' + 2tv - 1 = 0 or tv' + 2tv = 1. The left side is 2
recognized as (t v)' and thus we may integrate to obtain 2
tv = t + c (otherwise, divide both sides of the D.E. by 22 t and find the integrating factor, which is just t in
this case). Solving for v = dy/dt we find
2
dy/dt = 1/t + c/t so that y = lnt + c /t + c .
1 2
Set v = y', then v' = y" and thus the D.E. becomes
v' + tv2 = 0. This equation is separable and has the -1 2 2
solution -v + t /2 = c or v = y' = -2/(c1 - t ) where
c1 = 2c. We must consider separately the cases c1 = 0,
2
c1 > 0 and c1 < 0. If c1 = 0, then y' = 2/t or
y = -2/t + c2. If c1 > 0, let c1 = k . Then
y' = -2/(k-t ) = -(1/k)[1/(k-t) + 1/(k+t)], so that
y = (1/k)ln|(k-t)/(k+t)l+c2. If c1 < 0, let c1 = -k2.
2 2 -1 Then y' = 2/(k + t ) so that y = (2/k)tan (t/k) + c2.
Previous << 1 .. 328 329 330 331 332 333 < 334 > 335 336 337 338 339 340 .. 486 >> Next